Matrine Directly Activates Extracellular Heat Shock Protein 90, Resulting in Axonal Growth and Functional Recovery in Spinal Cord Injured-Mice - Tanabe, Norio; Kuboyama, Tomoharu; Tohda, Chihiro (Frontiers in Pharmacology, 2018)
After spinal cord injury (SCI), reconstruction of neuronal tracts is very difficult because an inhibitory scar is formed at the lesion site, in which several axonal growth inhibitors, such as chondroitin sulfate proteoglycans (CSPG), accumulate. We previously found that matrine, a major alkaloid in Sophora flavescens, enhanced axonal growth in neurons seeded on CSPG coating. The aims of this study were to investigate therapeutic effects of matrine in SCI mice and to clarify the underlying mechanism. Matrine was orally administered to contusion SCI mice. In the matrine-treated mice, motor dysfunction of the hindlimbs was improved, and the density of 5-HT-positive tracts was increased in the injured spinal cord. We explored putative direct binding proteins of matrine in cultured neurons using drug affinity responsive target stability (DARTS). As a result, heat shock protein 90 (HSP90) was identified, and matrine enhanced HSP90 chaperon activity. We then presumed that extracellular HSP90 is a matrine-targeting signaling molecule, and found that specific blocking of extracellular HSP90 by a neutralizing antibody completely diminished matrine-induced axonal growth and SCI amelioration. Our results suggest that matrine enhances axonal growth and functional recovery in SCI mice by direct activation of extracellular HSP90. Matrine could be a significant candidate for therapeutic drugs for SCI with a novel mechanism.